The experiences of undergraduates nursing students on academic support provided by the public nursing college during the COVID-19 lockdown in Gauteng Province - Du Plessis, Moselene (University of Pretoria, 2024)
Dissertation (Mcur (Nursing Clinical Fields of Study))--University of Pretoria, 2023.